Equalizing Scientific Literacy of Prospective Elementary Teacher through Science Process Skill (SPS)-based Science Matriculation - Hikmatunisa, Nenden Permas; Mulyani, Hanifah; Zulkarnaen, Rizki Hadiwijaya (International Conference on Elementary Education, 2025)
The role of elementary teachers in science education is crucial in developing students’scientific literacy. Teachers are also expected to be scientifically literate. However, existing studies indicates the scientific literacy of prospective elementary teachers is still classified moderate as a gapfound among them. This research was aimed to obtain a comprehensive overview of Science Process Skill (SPS)-based science matriculation implemented to equalize scientific literacy of prospective elementary teachers. The method used was a mix method with a convergent parallel design where both quantitative and qualitative data are collected simultaneously, analyzed separately, and interpreted as integrated results. The research subjects were 24 first semester students of PGSD study program taken through purposive sampling. The Wilcoxon test showed a Z-value of 269.0 with an Asymp. Sig. (2-tailed) < 0.001, indicating a significant difference between pretest and post-test scores. The average post-test score increased by 16.9 points after completing the matriculation. Further analysis of N-gain score was conducted to evaluate the effectiveness of matriculation. The results of the t-test showed a significant difference with a comparison value of 0.70 (t(23) = -10.3, p < 0.001), indicating that the effectiveness ofscience matriculation can be still improved to meet the better result.